Book Review: Copyright for Schools: A Practical Guide, 6th Edition - Dickson, Katherine (Journal of Copyright in Education & Librarianship, 2021)
New for 2021 is the sixth edition of Copyright for Schools: A Practical Guide, by Carol Simpson and Sara E. Wolf. Ms. Simpson is an attorney and former professor of library and information science, with additional experience as a school librarian, teacher, and district library administrator. Ms. Wolf is a professor in Auburn University’s College of Education, with research interests in library media and technology and experience in institutional copyright policy development. The book is designed to address the copyright issues and questions that tend to arise for K-12 teachers, school librarians, and school administrators, though librarians in other contexts such as public libraries and higher education would likely find its contents useful too. The sixth edition updates previous editions by adding content on the copyright implications of streaming video services and cloud computing, issues related to disability, responding to cease-and-desist letters, openly licensed resources and Creative Commons licenses, and the implications of the Music Modernization Act. The latest edition of the book also contains a concordance (a table of legal citations and the principles for which they stand), and more robust legal citations than previous editions.